DMFT Index and limitation in speaking clearly in 12-year-old schoolchildren, Cuenca-Ecuador. - Toledo-Silva, Jonathan Steven (2020)
Objective: To determine the relationship between the decayed/missing/filled teeth (DMFT) index and self-perceived limitation in speaking clearly in 12-year-old schoolchildren from the ¨El Batán¨ parish in Cuenca-Ecuador. Materials and methods: This was an observational study, with a retrospective relational level, consisting of 154 reports, corresponding to 104 girls and 50 boys. The DMFT variables and limitation to speak clearly were analyzed by descriptive statistics and correlation was determined by means of the Kendall's Tau-b statistical test. Results: The DMFTindex was very low with 32.5%, followed by a medium of 29.5%; while the impact of the limitation to speak clearly affected 35.6% of the females and 46.0% of the males. The relationship between the DMFT index and the limitation to speak clearly was significant (p = 0.000), with a low positive association (0.301). It was also significant according to gender and with a medium association for boys (0.413) and low association for girls (0.261). Conclusion: About one third of schoolchildren showed a low and medium DMFT index. Less than one third of the children studied reported some limitation to speak clearly. There was a correlation between a higher index of dental cavities and a greater self-perceived limitation to speak clearly, although this association was low, affecting boys more frequently than girls in this urban area.